2010
DOI: 10.1158/0008-5472.can-09-2447
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Integrin Effector Kinase Focal Adhesion Kinase in Cancer Cells Is Regulated by Crosstalk between Protein Kinase Cα and the PDZ Adapter Protein mda-9/Syntenin

Abstract: Aberrant adhesion signaling pathways in cancer cells underlie their deadly invasive capabilities. The adhesion-related PDZ adapter protein mda-9/syntenin is a positive regulator of cancer cell progression in breast cancer, melanoma, and other human cancers. In this study, we report that mda-9/syntenin mediates adhesion-mediated activation of protein kinase Cα (PKCα) and focal adhesion kinase (FAK) by fibronectin (FN) in human breast cancer and melanoma cells. FN rapidly stimulated the expression of mda-9/synte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 40 publications
5
64
0
Order By: Relevance
“…Plasmids and RNA Interference-Expression vectors for FLAG-tagged mda-9/syntenin, PKC␣, the dominant negative (DN)-PKC␣, and DN-Rac1 were described previously (15). Expression vectors for the FLAG-Akt, DN-Akt, and DN-PI3K were obtained from Dr. N. Fujita (Japanese Foundation for Cancer Research, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmids and RNA Interference-Expression vectors for FLAG-tagged mda-9/syntenin, PKC␣, the dominant negative (DN)-PKC␣, and DN-Rac1 were described previously (15). Expression vectors for the FLAG-Akt, DN-Akt, and DN-PI3K were obtained from Dr. N. Fujita (Japanese Foundation for Cancer Research, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…All constructs and mutations were confirmed by DNA sequencing. The pSUPER shRNA-producing plasmids (pSUPER/syntenin and pSUPER-scramble) were previously described (15). siRNAs for mda-9/syntenin, ILK and scramble control were from Santa Cruz Biotechnology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that TM4SF1 is associated with poor prognosis in squamous lung carcinoma (21) and mesothelioma (22). In addition, TM4SF1 combines with synthenin-2, which promotes melanoma and breast-cancer metastasis by activating protein kinase C and focal adhesion kinase/Src family kinase signaling (23)(24)(25).…”
Section: A Gain-of-function Platform For the Identification Of Canonimentioning
confidence: 99%
“…Integrin was reported to regulate EMT via focal adhesion kinase (FAK) (23) or integrin linked kinase (ILK) (24). The signaling of PI3K/AKT (25), WNT (26), and rAS/mAPK (27) are all downstream targets of integrin signaling. Members of the Rho GTPase family are mainly involved in the regulation of cytoskeletal and cell adhesion (28); RhoGDI is an important negative regulator of Rho GTPase.…”
Section: Discussionmentioning
confidence: 99%